Location vs academic performance of school: parental decision in sustaining the future of their children, the case study of Gombak district - Mohamed Osman, Mariana; Bachok, Syahriah; Mohd Ibrahim, Nuraihan (2015)
This paper presents the assessment on parents’ criteria in selecting public schools to enroll their children in public schools within Gombak District. The topic of school development and planning is relevant to achieve sustainable development in urban planning. Planning of school is one of the major elements in a comprehensive development planning process as it serves the needs of the community. School selection is always a concern in the school development especially in term of capacity and quality. However, school development planning faced with many obstacles that need to be improved on the school development and management. The main criteria in determining the school selection are location, distance, school facilities, academic school’s performance, extra-curricular activities and school environment. The data collected through questionnaire survey method. In this study, the sample size is of 400 respondents who will be handed out specifically for parents that send their children to the public schools. The samples are entered to Statistical Package of Social Sciences (SPSS) software. The result then analyzed based on Descriptive and Inferential Statistics approach. The study identified academic school’s performance is the most important criteria of parents in the school selection for enrolling their children while the extra co-curricular activity is the least important criteria for them. From the findings, this research proposes recommendations to overcome the issues and problems with the public school development in Gombak District. Therefore, it will lead to the improvement of the school planning to cater primary needs for educations at various levels as well to improve the quality of life of the community.